Efficacy and Safety of High Dose of Losartan Versus Indapamide with Standard Dose of Losartan in Hypertensive Patients Uncontrolled by Standard Dose of Losartan - Rudra, Sujan; Das, Nabanita; Sarawat, Sefa; Urmi, Rehnuma; Rana, Mashud (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Antihypertensives are a class of drugs that are used to treat hypertension. This study compared the antihypertensive efficacy and safety of Losartan and Indapamide combination therapy with high-dose Losartan (100 mg) therapy in hypertensive patients uncontrolled by a standard dose of Losartan. Materials and methods: The study was conducted with 108 patients in the Department of Pharmacology and Therapeutics and the Department of Medicine of Chittagong Medical College Hospital (CMCH) from July 2021 to December 2021. Patients were divided into two groups: Group A, which increased the dose of Losartan (100 mg), and Group B, which combined Losartan (50 mg) and Indapamide (1.5 mg). Results: The study found that serum creatinine and uric acid significantly differed in both groups before and after treatment, with a p-value of 0.000. However, there was no significant difference in serum electrolytes Na+, K+, urine albumin, and ECG at baseline and 12 weeks after intervention. Before treatment, 59.3% of patients had urine abnormalities (Albuminuria) and 26.9% had ECG changes. After treatment, these figures increased to 69.4% and 30.6%, respectively, with no significant difference. Smokers (22.20%) had a substantial relation with raised SBP (164.70±17.32) and DBP (104.13±8.62) at a 1% level of significance, while alcohol had a significant (10.20%) association with raised SBP (164.48±13.43) at a 5% significance level. And in 3 follow up SBP and DBP had a significant improvement. Combining Losartan 50 mg and Indapamide 1.5 mg improves patients' conditions by reducing blood pressure. Conclusion: The combination of ARBs and diuretics offers advantages in managing hypertension. They effectively lower BP for at least 12 weeks, has an excellent efficacy profile, and may provide benefits beyond BP reduction alone. JCMCTA 2023 ; 34 (1) : 64-68